Wydatki na edukację jako czynnik konkurencyjności gospodarek rynkowych - Dobrzański, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
International competitiveness is a frequent topic in the world’s economic literature. Nowadays, attention is also drawn to the efficiency of the economy as an addition to a comparative analysis of economies. The paper presents different approaches to competitiveness and effi ciency of the economy and their measurement. The study includes an analysis of one of the major factors of competitiveness of economies — education. Calculations were performed using the DEA method.
Keywords: competitiveness; efficiency; relative effectiveness; DEA efficiency method; education